STUDY ON ENVIRONMENTAL ATTITUDES AND PASSENGER PREFERENCES FOR BALI’S PLANNED URBAN RAIL (Jurnal Ilmiah Teknik Sipil, 2026)
Bali is experiencing increasing traffic congestion, growing travel demand, and rising environmental pressures, which highlight the need for more sustainable transport solutions. The planned urban rail system is expected to play a significant role in addressing these challenges as an alternative mode with lower environmental impacts. Understanding how environmental attitudes influence passenger behaviour is therefore important in assessing the potential acceptance of the system among different user groups. This study aims to examine how environmental influence passengers’ willingness to pay (WTP) and their priority for using Bali’s urban rail system. In particular, the research explores whether higher environmental awareness encourages a stronger preference and whether there are behavioural differences among residents, domestic tourists, and international tourists on the proposed service.A stated preference (SP) survey hence conducted both online and on-site between June and July 2025, bring in 1,186 valid responses. Ordered logit models were applied to analyse the determinants of urban rail priority and WTP, incorporating socio-demographic characteristics, trip attributes, travel costs, and levels of environmental awareness.The findings indicate that the factors shaping urban rail priority differ across groups. Residents are primarily influenced by trip-related characteristics, while domestic tourists are affected by a broader range of socio-demographic factors. International tourists exhibit similar sensitivities but with a stronger emphasis on environmental considerations. Higher environmental awareness generally increases the likelihood of prioritising urban rail, although this effect is statistically significant mainly for international tourists. WTP results show that approximately 75% of respondents are willing to pay more than the baseline fare suggested from previous feasibility study. While cost remains the dominant determinant of WTP, environmental attributes play more role for international tourists.
Keywords: Urban Rail; Bali; Stated Preference; Willingness to Pay; Environmental Awareness